Panca Indera dalam Epistemologi Islam - Muhammad Taqiyuddin (Tasfiyah: Jurnal Pemikiran Islam, 2020)
This study was library research through several-mixed literature from Islamic doctrine which had been explained by several philosophers, jurist, also the sufis account. Rather than reconstructing its literal form, these Islamic thinkers based on Quranic revelation developed rational elucidation about five senses and their places in Islamic epistemological doctrine. This research found that Islamic tradition affirmed five senses as one of basic of human understanding. But, these potencies were given from Allah to the mankind for their capability to understand God’s sign. Which these signs can provide human understanding about physical reality as mere aspects of God’s sign in this physical world (dunyā). Furthermore, these understanding can be developed as true knowledge; wich will be asked at the day of judgement (qiyāmah).